A new mesogenic fluorene derivative: 2, 7-bis(4-pentylphenyl)-9, 9-diethyl-9H-fluorene. Issue 4 (16th March 2019) - Gupta, Sakuntala; Choudhury, Tanmay; Dmochowska, Ewelina; Kula, Przemysław; Borbone, Fabio; Centore, Roberto
ABSTRACT: The title compound, 2, 7-bis(4-pentylphenyl)-9, 9-diethyl-9H-fluorene, is a new mesogenic compound containing the fluorene moiety. It exhibits a monotropic nematic liquid crystalline behaviour, with isotropisation temperature of 53°C. The compound is also polymorphic in the solid state, with one crystal phase melting at 103°C and another one melting at 71°C. The crystal and molecular structure of the high melting solid phase have been determined from single crystal X-ray diffraction analysis. Crystals are monoclinic, with cell dimensions a = 16.649(6) Å, b = 8.305(3) Å, c = 24.598(7) Å, β = 111.60(2)⁰, space group P 21 /c and four molecules in the unit cell. Refinement leads to R = 0.0558. The two terminal alkyl chains and one phenyl ring are disordered over two split positions. The imbricated molecular packing observed in the solid state seems to resemble that of the nematic phase that is formed upon cooling the melt. Graphical Abstract: